Role of Self-Help groups in supporting Agriculture in India: An Empirical Study - SRIVASTAV, SHASHANK (International Journal of Psychosocial Rehabilitation, 2024)
In India, self-help groups (SHGs) have become a crucial forum for advancing and supporting agriculture. These groups are typically made up of people from rural areas who gather together to share resources and knowledge in order to accomplish shared objectives. The main goal of SHGs in agriculture is to increase the income and productivity of small and marginal farmers, who make up the bulk of Indian farmers. SHGs serve as a link between farmers and other governmental and non-governmental groups that offer farmers technical and financial support. They support farmers in obtaining loans, knowledge about cutting-edge farming methods, and markets for their produce. SHGs help farmers adopt new technology and farming techniques by giving them a forum to exchange experiences and learn from one another. Initiatives have been essential in empowering rural communities and giving farmers sustainable means of subsistence. Overall, SHGs have played a critical role in assisting India’s agriculture sector in addressing issues encountered by small and marginal farmers and advancing inclusive and sustainable development in rural areas. The sample size of the study was 171 respondents. The data analysis was performed with the help of t-test and mean. The sample size of the study was 171 respondents. The data analysis was performed with the help of t-test and mean